Uso e necessidade de prótese dentária aos 24 anos numa coorte de nascimentos: prevalência e fatores associados - Corrêa, Marcos Britto (2009)
This study aimed to investigate the prevalence of use and needs of dental prosthesis at age 24 and determinants of needs of dental prosthesis in this population. The study was nested in a population-based birth cohort started in 1982 in Pelotas, Brazil. A representative sample of 720 young adults was evaluated. Dental examinations and interviews were performed at 15 and 24 years old. Use and need of prosthesis was the outcome. Exploratory variables included demographic and socioeconomic (at birth, 15 and 24 years old), oral health and dental service utilization patterns (at ages 15 and 24). Prevalence of outcomes was calculated and Poisson Regression was used to determine risk factors to needs of dental prosthesis. The prevalence of use and needs of dental prosthesis was 2.08% and 29.72%, respectively. Multivariable analysis showed that poorest family socioeconomic trajectory [PR= 1.56 IC95% (1.08-2.26)], lower mother s educational level at children birth (p=0.023), lower family income at children birth [RP= 1.37 (1.01-1.86)], no oral hygiene instruction by the dentist [RP=1.64 IC95% (1.11-2.41)] and caries presence (high DMFT tertile) (p<0,001) were associated with prosthetic treatment needs. The results of this study support the hypothesis that socieconomic, behavioral and clinical determinants were associated to the need of dental prosthesis